Heterogenous Dose-escalated Prostate Stereotactic Body Radiation Therapy for All Risk Prostate Cancer: Quality of Life and Clinical Outcomes of an Institutional Pilot Study. (July 2020) - Parsai, Shireen; Juloori, Aditya; Sedor, Geoffrey; Reddy, Chandana A.; Thousand, Richard; Magnelli, Anthony; Berglund, Ryan K.; Stovsky, Mark; Klein, Eric A.; Tendulkar, Rahul D.; Stephans, Kevin L.
Abstract : Objectives: Previous prostate stereotactic body radiation therapy studies delivered uniform doses of 35 to 40 Gy/5 fx. Attempts at uniform dose escalation to 50 Gy caused high rates of gastrointestinal (GI) toxicity. We hypothesize that heterogeneous dose escalation to regions nonadjacent to sensitive structures (urethra, rectum, and bladder) is safe and efficacious. Materials and Methods: Patients were enrolled on a prospective pilot study. The primary endpoint was treatment-related GI and genitourinary (GU) toxicity. The secondary endpoints included quality of life (QOL) assessed by the EPIC-26 questionnaire and biochemical control. The target volume received 36.25 Gy/5 fx. The target >3 mm from sensitive was dose escalated to 50 Gy/5 fx. Results: Thirty-five patients were enrolled. Three patients had low, 14 intermediate, and 18 high-risk disease. The mean initial prostate specific antigen was 15.1 ng/mL. Androgen deprivation therapy was given to 19 patients. Median follow-up was 46 months. Urinary irritation/obstructive and urinary bother scores declined by minimal clinically important difference threshold from baseline at 6 weeks, but subsequently recovered by 4 months. No differences in QOL scores were observed for urinary incontinence, bowel domain, bloody stools, or sexual domain. One patient developed acute grade 4 GU toxicity and acute grade 4 GI toxicity. The incidence of late high grade toxicity was 1/35 for GU toxicity and 2/35 for GI toxicity. Freedom from biochemical failure at 3 years was 88.0%. Conclusions: Heterogeneous dose-escalated prostate stereotactic body radiation therapy is feasible with low rates of acute and late toxicities and favorable QOL outcomes in patients with predominantly intermediate-risk and high-risk prostate cancer.